Predictive modeling of suddenly expanded flow process in the Supersonic Mach number regime using response surface methodology - Quadros, Jaimon Dennis; Khan, Sher Afghan; Antony, A J (Institute of Institutional Industrial Research, 2017)
The present work uses design of experiments (DOE) technique along with response surface methodology to develop linear models, to establish linear input-output relationships in a suddenly expanded flow process. Mach number (M), nozzle pressure ratio (NPR), area ratio (AR) and length to diameter (L/D) ratio have been considered as the input parameters, which controls the output (i.e. base pressure). Full factorial DOE has been implemented for developing the linear model. Experiments were conducted to measure base pressure by two means i.e. without control (WoC) and with the use of active control (WC). The adequacy of developed models was checked through statistical analysis. Fifteen random test cases were conducted in order to validate the models. It is observed that, both linear regression models for base pressure without and with control are statistically adequate and capable of making accurate predictions.